PENGARUH GOOD COORPORATE GOVERNANCE, UKURAN PERUSAHAAN DAN PENGHINDARAN PAJAK TERHADAP MANAJEMEN LABA - Yunus Nurhasan; Rijal Arslan; Rananda Septanta; Muhammad Eko Ari Wibowo (Unversitas Prof. Dr. Moestopo (Beragama), 2023)
This study aims to determine the effect of good corporate governance, company size and tax evasion on earnings management during the 2018 – 2022 period, which obtained 30 data in this study. The type of data used is secondary data, in the form of the company's annual report. Data analysis used descriptive statistics, classical assumption test, coefficient of determination and multiple linear regression analysis. Data processing uses the SPSS program to perform multiple linear regression analysis, coefficient of determination, normality test, multicollinearity test, autocorrelation test and hypothesis test. The results of this study indicate that the results of the study show that the data meet the classical assumptions such as normal distribution data, no multicollinearity, no heteroscedasticity and no autocorrelation. From the results of the hypothesis that partially good corporate governance and tax avoidance have no effect on earnings management and company size has a significant influence on earnings management.